I'm so sorry if these are wrong...
1. y=-7/5x-3
2. y=1x+6
3. y=5/4x-8
4. y=1/4x-2
5.y=-5x-2
6. y=-2/5x-3
7. y=5x+19
8. y=2x-6
9. y=-4/5x-5
10. y=-4/5x+4
Kelly bought a new car for $20,000. The car depreciates at a rate of 10% per year. Write an equation to model the car's value.
y=20,000-.10x
with x being the number of years
Answer:
[tex]y=\$20,000\cdot (0.90)^x[/tex]
Step-by-step explanation:
We have been given that Kelly bought a new car for $20,000. The car depreciates at a rate of 10% per year. We are asked to write an equation to model the car's value.
Since car's value depreciates by 10% per year, so value of car is depreciating exponentially.
We know that an exponential decay function is in form [tex]y=a\cdot (1-r)^x[/tex], where
a = Initial value,
r = Decay rate in decimal form.
Let us convert 10% into decimal form as:
[tex]10\%=\frac{10}{100}=0.10[/tex]
Upon substituting our given values in decay formula, we will get:
[tex]y=\$20,000\cdot (1-0.10)^x[/tex]
[tex]y=\$20,000\cdot (0.90)^x[/tex]
Therefore, our required equation would be [tex]y=\$20,000\cdot (0.90)^x[/tex].
The 4 people in your crew each spent 4 hours laying sod. How many person-hours is this?
Since there are 4 people and they each spent 4 hours working, all we have to do is multiply the number of people (4) by the amount of hours each person spent (4)
4 x 4 = 16
Therefore, the total amount of hours is 16
Hope this helps you
-AaronWiseIsBae
Answer:
16 hours
Step-by-step explanation:
Given: There are 4 people in your crew.
Each spent 4 hours of laying sod.
To find the person hours, we have to multiply the number of people (4) by the amount of hours each person spent (4).
Total number of hours = Number of persons * Number of hours spent
Total number of hours = 4 x 4 = 16 hours
Therefore, the total amount of hours is 16.
Lamar is solving the equation x^2 - 12x = -6 by completing the square. Which shows lamar's next step and the solution to the equation?
step 1: x^2 -12x = 6
step 2: x^2 - 12x + 36 = -6 +36
Answer:
[tex]x^2-12x+36= -6+36[/tex]
Step-by-step explanation:
Equation : [tex]x^2-12x = -6[/tex]
General equation : [tex]ax^2+bx+c=0[/tex]
So,we need to add and subtract [tex](\frac{b}{2})^2[/tex] for completing square.
So, next step of completing square :
[tex]x^2-12x+6^2-6^2= -6[/tex]
[tex]x^2-12x+36= -6+36[/tex]
Hence Step 2 shows lamar's next step and the solution to the equation
The solution to the equation after completing the square is:
(x - 6)² = 30
How to find the next stepLamar starts with the equation x² - 12x = -6.
Step 2: To complete the square, Lamar takes the coefficient of the x term, which is -12, divides it by 2, and then squares it. In this case, (-12/2)² = 36.
Lamar adds 36 to both sides of the equation to maintain its balance. By doing so, he effectively creates a perfect square trinomial on the left side of the equation.
x² - 12x + 36 = -6 + 36
Simplifying the right side, -6 + 36 equals 30.
The equation now becomes:
x² - 12x + 36 = 30
Now, Lamar can rewrite the left side of the equation as a perfect square. The left side is (x - 6)² because (x - 6)(x - 6) equals x² - 12x + 36.
(x - 6)² = 30
Thus, the solution to the equation x² - 12x = -6, after completing the square, is (x - 6)² = 30.
Learn more about equation at
https://brainly.com/question/29174899
#SPJ6
What are the discontinuities of the function f(x) = the quantity x squared minus 36 over the quantity 4x plus 24?
there is a point discontinuity ( hole ) at (- 6, - 3 )
factor the numerator/denominator
f(x) = [tex]\frac{(x-6)(x+6)}{4(x+6)}[/tex]
the factor (x + 6) cancels leaving the simplified version of f(x)
f(x) = [tex]\frac{x-6}{4}[/tex]
the removal of the factor (x + 6) from the numerator/denominator means there is a discontinuity at x + 6 = 0 , that is x = - 6
f(- 6 ) = [tex]\frac{-6-6}{4}[/tex] = - 3
there is a point discontinuity ( hole ) at (- 6, - 3 )
A babysitter earns 8.50$ for 1 hour and 34$ for 4 hours if she works 18.5 hours one weekend what was her earning for the weekend
Select the multiplication sentence that applies the associative property of multiplication to the example. Example: 6 × (4 × 2) = 48 A. (6 × 7) + 6 = 48 B. 6 × (4 + 2) = 36 C. (6 + 4) × 2 = 20 D. (6 × 4) × 2 = 48
answer : D
A. (6 × 7) + 6 = 48
Associative property of multiplication . Here we have +6 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
B. 6 × (4 + 2) = 36
Here we have 4 +2 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
C. (6 + 4) × 2 = 20
Here we have 6 + 4 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
D. (6 × 4) × 2 = 48
Here we have 6 times 4 times 2. so it comes under Associative property of multiplication
Alonzo's gas tank is 1/3 full. After he buys 3 gallons of gas, it is 1/2 full. How many gallons can Alonzo's tank hold?
Allen score in the video game was changed by -75 points because he miss some targets he got -15 points for each miss target how many targets did he miss
Answer:
he missed 5 targets
Step-by-step explanation:
A bookstore buys algebra 1 books at a wholesale price of $17 each. It then marks up the price by 55%, and sells the algebra 1 books. What is the amount of the markup? What is the selling price?
The amount of markup is $9.35 .The selling price of algebra1 books after 55% increment is $26.35
What is the method to calculate x% increment?If there is x% increment in y then the increment will be (x/100)*y and the new amount after x% increment will be now y + (x*y)/100
A bookstore buys algebra 1 books at a wholesale price of $17 each.
Initial price of algebra 1 book was = $17
There is 55% increment in books price before selling
55% of initial price = (55/100)*17 = 935/100= $9.35
The selling price = wholesale price + 50% increment = 17 + 9.35 =26.35
Therefore, the amount of markup or increment is $9.35 the selling price of the algebra 1 books after 55% markup is $ 26.35.
Also, Learn more about the percentage increment from the link below:
brainly.com/question/27758670
#SPJ2
3. At a bargain store, Tanya bought 3 items that each cost the same amount. Tony bought 4 items that each cost the same amount, but each was $2.25 less than the items that Tanya bought. Both Tanya and Tony paid the same amount of money. What was the individual cost of each person's items?
(a) Write an equation. Let x represent the cost of one of Tanya's items.
(b) Solve the equation. Show your work.
(c) Check your solution. Show your work.
(d) State the solution in complete sentences.
By setting up an equation with x as the cost of Tanya's items, we find that each of Tanya's items cost $9.00. Tony's items, being $2.25 cheaper, cost $6.75 each. The solution is checked by ensuring both Tanya's and Tony's total expenditure was equal.
The question asks us to find the individual cost of items purchased by Tanya and Tony at a store, given that Tony's items each cost $2.25 less than Tanya's but both spent the same amount overall.
Equation Setup
Let x represent the cost of one of Tanya's items. Since Tanya bought 3 items, she spent 3x dollars. Tony's items each cost $2.25 less, so they cost (x - $2.25) each. Tony bought 4 items, spending 4(x - $2.25). Since both spent the same amount:
3x = 4(x - $2.25)
Solving the Equation
To solve for x:
Distribute the 4 on the right side of the equation to get 3x = 4x - $9.00.Subtract 4x from both sides to get -x = -$9.00.Divide both sides by -1 to get x = $9.00.So, each of Tanya's items cost $9.00.
Checking the Solution
To verify:
Tanya's total is 3($9.00) = $27.00.Tony's total is 4($9.00 - $2.25) = 4($6.75) = $27.00.Both totals match, confirming that the solution is correct.
Tanya's items each cost $9.00, while Tony's items, costing $2.25 less, each cost $6.75.
What is the solution to the system of equations?
-3 x - 4y - 3z= -7
, 2x - 6 y + 2z= 3,
5 x - 2y + 5 Z=9
Answers:
A, (5, -2, 7)
B, (-5, 2, 7,)
C, (5,2,-7)
D, No solution
Solution
Step 1: Isolate the variable x and plug in the values of x in the second and third equations.
Step 2: Isolate variable y and solve for y.
We get the value of y = 5/26
When we substitute the value of y , 1 = 0 which is not true.
Therefore, this system has No Solution.
Answer: No solution
Geometry help , only answer if your sure please. The question is in the attached
J(1 , 0); N(5, 0) ; M(5 , -3) and P(2 , -5)
Translation (x,y) -->(x-4, y+4)
J'(-3,4), N'(1, 4) ; M'(1 , 1) and F'(-2 , -1)
Answer is C)
J'(-3,4), N'(1, 4) ; M'(1 , 1) and P'(-2 , -1)
3( x -5)- 5x= 25+ 6x What is the answer and how do you solve this??
To solve this equation, distribute, combine like terms, and isolate the variable, x.
Explanation:To solve this equation, we need to simplify both sides and isolate the variable, x.
Starting with the left side, distribute the 3 to the terms inside the parentheses: 3x - 15 - 5x = 25 + 6x.
Combine like terms on both sides of the equation: -2x - 15 = 25 + 6x.
Add 2x to both sides of the equation and add 15 to both sides: -15 - 25 = 6x + 2x.
Simplify the equation: -40 = 8x.
Finally, divide both sides by 8 to solve for x: x = -5.
Learn more about Linear equations here:https://brainly.com/question/32634451
#SPJ2
How would i number the graph
A lecture hall seats 220 people. If 99 people are in the lecture hall, what percentage of the seats are filled?
Answer:
45%
Step-by-step explanation:
To find the percent, we write the information as part/whole:
99/220
Now we convert to a decimal by dividing:
99/220 = 99÷220 = 0.45
Lastly, multiply by 100:
0.45(100) = 45
Find 0.45 of 80 A.36 B.3.6 C.0.36 D.0.036
A
the word 'of' means to multiply
0.45 × 80 = 36
15 points all other rewards will be given please no non-scene
uoy knaht
Consider these three numbers written in scientific notation.
1.67 x 10-4
9.7 x 10-6
4.5 x10-9
Which shows the numbers in order from least to greatest?
A.
1.67 x 10-4 ,
9.7 x 10-6,
4.5 x 10 -9
B.
4.5 x 10-9,
9.7 x 10-6 ,
1.67 x 10 -4
C. 1.67 x10 -4 ,
4.5 x 10-9 ,
9.7 x 10-6
D. 9.7 x 10-6 ,
4.5 x 10-9,
1.67 x 10-4
Why hello there
The correct answer is B
If my answer helped please mark me as brainliest thank you and have the best day ever!
Simplify the expression given below.
x-3/x-1 + 6/x-3
Answer:
Step-by-step explanation:
x2+3/x2-4x+3
Answer:
x^2+3/(x-1)(x-3)
Step-by-step explanation:
Principal: $750,00; annual interest rate: 5 percent. What is the interest after 6 months?
Final answer:
To calculate the interest after 6 months with a principal of $750,000 and an annual interest rate of 5%, you need to convert the annual rate to a monthly rate and then use the formula Interest = Principal × Rate × Time. The interest after 6 months is $1,562.50.
Explanation:
To calculate the interest after 6 months, we can use the formula:
Interest = Principal × Rate × Time
Here, the principal is $750,000, the annual interest rate is 5%, and the time is 6 months.
First, we need to convert the annual interest rate to a monthly rate:
Monthly interest rate = Annual interest rate / 12
Monthly interest rate = 5% / 12 = 0.4167%
Now, we can calculate the interest:
Interest = $750,000 × 0.4167% × 6/12
Interest = $1,562.50
WILL GIVE BRAINLIEST!!! PLEASE HELP!
write a mathematical equation stating that three consecutive even integers add up four times the smallest
PLEASE HELP!!!!!!!!!!!!!!!
Hey there!!
Let's take the first number an the smallest number as ' x '
Then, the second consecutive even integer would become ' x + 2 '
Third integer ' x + 4 '
Hence, adding them up, we get,
x + x + 2 + x + 4
... 3x + 6
This is equal to 4 times the smallest number.
We got the smallest number as ' x '
Hence, the final equation :
... 3x + 6 = 4x
Hope my answer helps!!
Patients who are addicted to cocaine are sometimes using the drug to combat depression. As such, sometimes addicts are given antidepressant medications to prevent relapse. A three-year study compared the effects of two such medications, lithium and desipramine, along with a placebo for 72 cocaine users wishing to break the habit. The patients were put into 3 groups of 24, and given 1 of the 3 treatments at random. This two-way table illustrates the results.
Treatment Relapse No relapse Total
Desipramine 10 14 24
Lithium 18 6 24
Placebo 20 4 24
Total 48 24 72
Give a conditional relative frequency for relapse among patients who took lithium.
A. 18/72 = 25%
B. 27/72 = 33.33%
C. 18/24 = 75%
D. 48/72 = 66.67%
Answer:
Option C, 18/24 = 75%
Step-by-step explanation:
Patients who were addicted to cocaine were divided into 3 groups of 24.
Each group was treated with three different drugs. One group of 24 patients were put on Lithium for treatment out of 24 patients who relapsed were 18.
So conditional relative frequency for relapse among patients who took Lithium would be :
Relative frequency of patients = (patients relapsed) / (total number of patients)
Relative frequency = [tex]\frac{18}{24}[/tex] = 75%
Option C, 18/24 = 75% would be the answer.
Running out of time! Please help and show work! Thank you! Will mark brainliest!
(-3j²k³)²(2j²k)³ = When a power is raised to a power the exponents have to be multiplied.
= (-3²j⁽²*²⁾k⁽³*²⁾)(2³j⁽²*³⁾k³) = We can take out the constants
= (9)(8)(j⁴k⁶)(j⁶k³) = We can group the same variables
= 72(j⁴j⁶)(k⁶k³) = When multiplying two powers that have the same base, you have to add the exponents.
= 72 j⁽⁴⁺⁶⁾k⁽⁶⁺³⁾ = 72j¹⁰k⁹
Answer = 72j¹⁰k⁹
Hope this helps!
[tex]\textit{\textbf{Spymore}}[/tex]
Use the complex conjugate to find the absolute value of 8+12i
A. 12
B.Square root of 208
C. Square root of 84
D. 8
Answer:
A. 12
Step-by-step explanation:
i= use complicated conjugate to search out definite quantity of 8 + 12i
i = 12i
i= twelve × ei 90°
i = twelve × (cos 90° + i sin 90°)
r = |i| = twelve
The absolute value of the complex number 8 + 12i is found by squaring the real part, squaring the imaginary part, adding these two results, and then taking the square root. This results in the square root of 208.
Explanation:The absolute value of a complex number a + bi is calculated through the formula sqrt(a² + b²). So, to find the absolute value of the complex number 8 + 12i, we substitute a with 8 and b with 12. We can perform the calculations as follows:
Square the real part, a: 8² = 64,Square the imaginary part, b: 12² = 144,Add the results: 64 + 144 = 208,Take the square root of the sum: sqrt(208). Thus, the absolute value is the square root of 208.Learn more about Complex Numbers here:https://brainly.com/question/20566728
#SPJ3
$1,200 is invested in an account earning 6.5% interest compounded annually. How much will there be in the account after 3 years?
Answer:
B. $1,449.54
Step-by-step explanation:
That's the answer
The average height of a female giraffe is4.6 meters What is her height in centimeters
460 cm
note that 1m = 100 cm, thus
4.6m = 4.6 × 100 = 460 cm
Which best describes the association between variables x and y?
A. Strong Positive
B. Strong Negative
C. Weak Positive
D. Weak Negative
Answer: C. Weak Positive
Step-by-step explanation:
In a scatter plot , a positive correlation is a relationship between the two variables x and y in which if value at x axis increases, then other value at y axis also increases.
In the given scatter plot the the association between variables x and y is a weak positive correlation because there is a lower likelihood in the relationship between variables.
What is the quotient of 59,584 divided 14
Answer:
4256
Step-by-step explanation:
Please help asap 25 pts
[tex]7x > -35\qquad|\text{divide both sides by 7}\\\\x > -5\\------------------------------------\\\\3x\leq30\qquad|\text{divide both sides by 3}\\\\x\leq10\\\\Answer:\ b)\ -5 < x\leq10[/tex]
A system of equations is given below:
(x+1)^2 + (y-4)^2 = 9
y=x+2
Which choice represents a solution to this system of equations?
A. (-2,0)
B. (1,-1)
C. (2,4)
D. (-1,4)
[tex]A.\ (-2,\ 0)\\\\substitute\ to\ y=x+2\\\\0=-2+2\\0=0\ CORRECT\\\\substitute \ to\ (x+1)^2+(y-4)^2=9\\\\(-2+1)^2+(0-4)^2=9\\(-1)^2+(-4)^2=9\\1+16=9\\17=9\ \ FALSE[/tex]
[tex]B.\ (1,\ -1)\\\\substitute\ to\ y=x+2\\\\-1=1+2\\-1=3\ \ \ FALSE[/tex]
[tex]C.\ (2,\ 4)\\\\substitute\ to\ y=x+2\\\\4=2+2\\4=4\ \ \ CORRECT\\\\substitute\ to\ (x+1)^2+(y-4)^2=9\\\\(2+1)^2+(4-4)^2=9\\3^2+0^2=9\\9+0=9\\9=9\ \ \ CORRECT[/tex]
[tex]D.\ (-1,\ 4)\\\\substitute\ to\ y=x+2\\\\4=-1+2\\4=1\ \ \ \ FALSE[/tex]
Answer: C. (2, 4)Which equation illustrates the additive inverse property?
A.
6 + 0 = 6
B.
6 + (-6) = 0
C.
6 × 0 = 0
D.
-6 + 6 = 6 + (-6)
Final answer:
The equation that demonstrates the additive inverse property is B. 6 + (-6) = 0, where 6 and -6 are additive inverses of each other.
Explanation:
The equation that illustrates the additive inverse property is B. 6 + (-6) = 0. The additive inverse property states that for any number 'a', there is a number '-a' such that 'a' plus '-a' equals zero. This is because adding a number to its additive inverse (which is the negative of the number) will result in zero.
Examples demonstrating the additive inverse include subtracting a positive number and changing its sign before operating the addition, for instance, 5-(+3) results in 5-3, which equals 2. Conversely, if you subtract a negative number, like subtracting -6 from 2, you would perform 2-(-6) which equals 2+6, resulting in 8.